Factors Associated with Husband's Assistance When Mothers Facing Childbirth at Tambusai Community Health Center - Dewi, Sri Sartika Sari; Nasution, Nurul Hidayah; Nasution, Izmi Fadhilah; Melfi Suryaningsih; Soleman Jufri (PT Inovasi Pratama Internasional, 2023)
Efforts to reduce anxiety during childbirth include the presence of a companion, such as a husband, biological mother, sibling or female friend of the mother. The presence of a second person or companion or birth attendant can provide comfort during childbirth. The presence of a companion during childbirth can have a positive effect on childbirth, namely reducing morbidity, reducing pain, shortening labor, and reducing the number of operative births including Caesarean section. The aim of this research is to determine the factors related to the husband's companion when the mother is facing childbirth at the Tambusai Community Health Center, Rokan Hulu Regency in 2023. This type of research is quantitative with a cross sectional design. The population in this study were all husbands of mothers giving birth at the Tambusai Health Center, Rukan Hulu Regency from March - July 2023. The sample in this study was 30 respondents using the total sampling method. The statistical test used is chi-square. The results show that the husband's age is related to the husband's assistance in the mother's birth process with a P value = 0.003 < 0.05. The psychological response of mothers giving birth is anxiety caused by pain during labor and can result in labor lasting a long time. Anxiety and pain in birthing mothers require support from their husbands during labor to provide a sense of security and comfort.